Modelling the determinants of voluntary repatriation: The role of ecosystem services in post-conflict reconstruction in Rakhine. (15th July 2021) - Aung, Thiri Shwesin; Unruh, Jon; Ali, Faizan
Abstract: Voluntary repatriation has the utmost importance in the contemporary understanding of refugee protection. Voluntary repatriation in safety and with dignity is considered to be the most desirable and durable solutions for refugees. However, voluntary repatriation represents increasingly daunting challenges to the refugees, the governments of both home and host countries, and implementing partners. The repatriation planning of Rohingya refugees is widely criticized as being profoundly premature and dangerous. Most of the refugees are set to return to destroyed villages where food and shelter are inadequate, ecosystem services overstretched, livelihood opportunities marginal and the physical environment unfit for human habitation. Investigating the view and perspectives of the refugees on the factors that influence their intention to return can inform the implementing actors to secure those conditions and ensure a durable solution. Here, we identify the conditions that influence the decisions by Rohingya refugees in protracted displacement regarding return to Myanmar. This research also addresses the dual challenges of repatriation and sustainable post-conflict reconstruction, and, more specifically, provides a framework on how to integrate ecosystem services in the repatriation process. Graphical abstract: Image 1 Highlights: Repatriation of Rohingya is criticized as being profoundly premature and dangerous. The physical environment in Rakhine is unfit for human habitation. This research addresses the dual challenges of repatriation and reconstruction. All the predictor variables are statistically significant and supported. Most of the refugees do not intend to return home.